Analysis of the prospect of heritage tourism in Kinta Valley, Perak (Malaysia) - Adnan Jusoh (Tanjong Malim, 2019)
Analysis of the prospect of heritage tourism in Kinta Valley, Perak (Malaysia) by Adnan Jusoh